Purification and characterisation of a typsin-like serine oligo peptidase from Trypanosoma congolense - Morty, R.E.; Authié, Edith; Troeberg, L.; Lonsdale-Eccles, John D.; Coetzer, T.H.T. (Elsevier, 1999)
Trypanosoma brucei contain a serine oligopeptidase (OP-Tb) that is released into (and remains active in) the blood of trypanosome-infected animals. Here a similar enzyme from Trypanosoma congolense is described. This oligopeptidase, called OP-Tc, was purified using three-phase partitioning, and ion-exchange and affinity chromatography. OP-Tc is inhibited by alkylating agents, by serine peptidase-specific inhibitors including 3,4-dichloroisocoumarin, 4-(2-aminoethyl) benzenesulfonylfluoride and diispropylfluoro-phosphate and by other peptidase inhibitors including leupeptin, antipain and peptidyl chloromethyl ketones. Reducing agents such as dithiothreitol enhanced activity as did heparin, spermine and spermidine. The enzyme has trypsin-like specificity since it cleaved fluorogenic peptides that have basic amino acid residues (Arg or Lys) in the P1 position. Potential substrates without a basic residue in P1 were not hydrolysed. Although OP-Tc has weak arginine aminopeptidase activity, the enzyme clearly preferred substrates that had amino acids in the P2 and P3 positions. Overall. OP-Tc appears to be less efficient than OP-Tb because it usually displayed lower Kcat/Km values for the substrates tested. However, like OP-Tb, the best substrate for OP-Tc was Cbz-Arg-Arg-AMC (Km=0.72 M, Kcat=96 s-1). OP-Tc preference for amino acids in the P2 position was (Gly, Lys, Arg) > Phe >Leu >Pro. The results also suggest that the P3-binding site has hydrophobic characteristics. OP-Tc may not be a naturally immunodominant molecule because neither IgG nor IgM anti - OP-Tc antibodies were detected in the blood of experimentally infected cattle.